Shariah compliance space planning for hotel room design - Saifuddin, Syaza; Othman, Rashidi; Md Hashim, Muhammad Hafizuddin Akmal; Jasmani, Ismail; Abdul Majid, Noor Hanita (World Academy of Science Engineering and Technology (WASET), 2015)
On the whole this research is to disseminate and illustrate the background of various concepts, approaches, terminologies used to describe the basic framework of an Islamic Resort. This paper will review the theoretical views in establishing a suitable and optimum environment for Muslim as well as non-Muslim guests in resorts while according to shariah. It involves a few research methodologies that requires the researcher to study on a few characteristics needed to create a new, better and more efficient in terms of social interaction, economic growth and other tolerable elements. Malaysia is an Islamic country and has billion of tourists coming over for business and recreational purposes. Therefore, having a conducive environment that best suit this target user is important in terms of generating the economy as well as providing a better understanding to the community on the benefits of applying these qualities in a conventional resort design. This study covered the topic of space planning in resort designs that is vital in creating a comfortable space for everyone. The number of people that are needed to make this change is huge, however, slowly, but surely, the result can be seen in the long run. In conclusion, it is important to take note that a lot of elements should be taken into consideration to create better flow and accessibility of the workers and guests. A shariah compliant space objective is to create a safer, more comfortable environment for everyone.